Advancing insights towards electrocatalytic activity of La/Ba-Sr-Co-Fe-O-based perovskites for oxygen reduction & evolution process in reversible solid oxide cell. (May 2023) - Dey, Shoroshi; Das, Suman; Chaudhary, Saroj; Parvatalu, Damaraju; Mukhopadhyay, Madhumita; Paul, Satadal; Das Sharma, Abhijit; Mukhopadhyay, Jayanta
Abstract: Electrocatalytic activity of La/Ba-Sr-Co-Fe-O-based mixed ionic and electronically conducting (MIEC) perovskites has been studied for selective oxygen reduction (ORR) and evolution (OER) processes applicable in Reversible Solid Oxide Cell (R-SOC). XPS study establishes scavenging of oxygen vacancy in LSCF and generation of the same in BSCF. BSCF enables faster oxygen ion transport and is correlated with lower frontier molecular orbital (FMO) energy gap of 1.18 eV derived from density functional theory (DFT). Relatively higher  ΔEFMO(Absolute) 1.75 eV in LSCF accounts for higher charge transfer. Amperometric measurements @800℃ in asymmetric cell configuration exhibit lowest time-dependent current loss of 0.019 mA.h -1 & 0.035 mA.h -1 for BSCF & LSCF under applied anodic (+0.8 V) and cathodic potentials (-0.8 V) for 200 h with respective surface resistances (Rs ) of 0.19 Ω.cm 2 and 0.081 Ω.cm 2 . H2 flux of 0.4Nl.h -1 .cm -2 obtained with BSCF, establishes its effectivity as OER whereas LSCF is found to be more selective in ORR. Graphical abstract: Image, graphical abstract